Human-centred design in UK asylum social protection - Michelle L. James; Rachel Forrester-Jones (University of Bath, Centre for Development Studies (CDS), 2022)
This paper considers United Kingdom welfare provision for asylum seekers in the context of social protection scholarship and policy discourse more commonly associated with international development. Social protection definitions are contested, ranging from those focused on state provision to wider interpretations reflecting debates on holistic wellbeing, human rights and self-actualisation. Most recently, the 2030 Agenda for Sustainable Development has called for social protection policies for all citizens to reduce inequality among and within countries. Though there is exigency to reduce the extreme inequality existing between countries, literature is lacking on how social protection can be used to critique inequality within more economically affluent nations. Commentaries on social protection also tend to focus on economic poverty, with less attention given to vulnerabilities such as marginalisation. Literature suggests that UK asylum welfare provision is based on deterrence, control and marginalisation. In response, and to encourage equity in how all countries' public policy is assessed, this paper utilises an international social protection framework to critique UK asylum welfare provision. It concludes by advocating for transdisciplinary, human-centred and comprehensive social protection policy design, encouraging participation by a wider range of stakeholders and a holistic understanding of wellbeing to meet asylum seekers' needs effectively and efficiently.
Keywords: 330; Asylum seeker; refugee; social protection; wellbeing